2022
DOI: 10.3389/fonc.2022.830420
|View full text |Cite
|
Sign up to set email alerts
|

miR-484: A Potential Biomarker in Health and Disease

Abstract: Disorders of miR-484 expression are observed in cancer, different diseases or pathological states. There is accumulating evidence that miR-484 plays an essential role in the development as well as the regression of different diseases, and miR-484 has been reported as a key regulator of common cancer and non-cancer diseases. The miR-484 targets that have effects on inflammation, apoptosis and mitochondrial function include SMAD7, Fis1, YAP1 and BCL2L13. For cancer, identified targets include VEGFB, VEGFR2, MAP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 133 publications
1
15
0
1
Order By: Relevance
“…miRNAs widely participate in signal activation, and cell proliferation, differentiation and death [ 35 ]. miR-484 is a key factor in cancer and non-cancerous diseases, and its targets in cancer include VEGFB, VEGFR2, MAP2, MMP14, HNF1A, TUSC5, and KLF12 [ 36 ]. miR-484 was found to precipitate tumorigenesis and metastasis in liver, prostate and lung cancers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs widely participate in signal activation, and cell proliferation, differentiation and death [ 35 ]. miR-484 is a key factor in cancer and non-cancerous diseases, and its targets in cancer include VEGFB, VEGFR2, MAP2, MMP14, HNF1A, TUSC5, and KLF12 [ 36 ]. miR-484 was found to precipitate tumorigenesis and metastasis in liver, prostate and lung cancers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-484 is a key factor in cancer and non-cancerous diseases, and its targets in cancer include VEGFB, VEGFR2, MAP2, MMP14, HNF1A, TUSC5, and KLF12 [ 36 ]. miR-484 was found to precipitate tumorigenesis and metastasis in liver, prostate and lung cancers [ 36 ]. Nan et al reported that in pancreatic ductal adenocarcinoma, the inhibitory effect of miR-484 on YAP was attenuated and predicted adverse patient outcomes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using the TNM stage system, miR-21 expression was higher in stages III and IV than in stages I and II; when using the BCLC staging system, miR-21 expression was higher in late BCLC stages C-D than in early BCLC stages 0-B ( 149 ). Another study showed that elevated miR-484 in serum could predict HCV-induced liver lesion progression and is strongly associated with shorter OS and PFS ( 189 ). In addition, increased levels of miR-122 in serum, predict a longer survival rate ( 196 ).…”
Section: Clinical Significance Of Ncrnas In Hccmentioning
confidence: 99%
“…МикроРНК-484 длиной 22 нуклеотида локализована в промоторной области гена MARF1 (meiosis regulator and MRNA stability factor 1) на хромосоме 16p13.11 в человеческом геноме. Физиологические функции miR-484 у млекопитающих многогранны и включают влияние на стресс эндоплазматического ретикулума, окислительный стресс, воспаление, пролиферацию клеток и апоптоз [8].…”
unclassified